Allopatric populations of the invasive larch casebearer differ in cold tolerance and phenology. (11th July 2019) - Ward, Samuel F.; Eidson, Erika L.; Kees, Aubree M.; Venette, Robert C.; Aukema, Brian H.
Abstract : 1. Traits of non‐native insect herbivores may vary spatially due to local genetic differences, rapid post‐introduction evolution, and/or novel host plant associations. 2. Populations of larch casebearer, Coleophora laricella Hübner, originally from Europe have likely been isolated for > 60 years in North America on eastern larch, Larix laricina (Du Roi) K. Koch, and western larch, Larix occidentalis Nutt. 3. This study investigated cold tolerance and phenology of larvae collected from eastern larch in Minnesota, and western larch in Oregon, Idaho, and Montana, U.S.A. 4. Mean supercooling points of larvae from Minnesota were up to 10 °C lower than supercooling points of larvae from Oregon, Idaho, and Montana. 5. At ambient environmental conditions in spring, overwintering larvae from Minnesota required a mean (± SE) of 172 ± 19 degree‐days above 5 °C to break winter quiescence and actively wander, significantly more than required by larvae from Oregon (66 ± 4), Idaho (64 ± 1), and Montana (60 ± 2). 6. Across all assays and despite substantial latitudinal and elevational variation among western larch sites, no significant differences in any traits were detected among larvae collected from western larch. 7. Spatial variation in cold tolerance and phenological traits of larch casebearer may be attributable to insect genetic differences and/or host plant effects, but exact mechanisms remain unknown. Differences in thermal biology between regions may result in disparate effects of climate change on insect populations and should be accounted for when forecasting insect dynamics across large spatial scales. Abstract : Mean supercooling points of larch casebearer larvae from eastern larch were up to 10 °C lower than supercooling points of larvae from western larch. Spring activity of overwintering larvae from eastern larch was delayed by > 100 degree‐days above 5 °C compared with larvae from western larch. Across all assays and despite substantial latitudinal and elevational variation among western larch sites, no significant differences in any traits were detected among larvae collected from western larch.